Protoneobisium basilice (Neobisiidae, Pseudoscorpiones): A new cave false scorpion from mt. Biokovo, Croatia - Ćurčić B.P.M.; Dimitrijević R.N.; Rađa T. (Archives of Biological Sciences, 2008)
A new species of the endemic pseudoscorpion genus Protoneobisium Ćurčić, 1988, P. basilice sp. n. from Croatia has been found, described and diagnosed. From its phenetically close congener, P. biocovense (Müller, 1931), the new taxon differs in many respects of both qualitative and quantitative nature. Both species of Protoneobisium have a limited distribution; they inhabit Mt. Biokovo, Croatia, and are probably the remnants of some ancient Maditerranean fauna of pre-Tertiary origin.